Silicon Nanoparticles Embedded in Nitrogen‐doped Hard Carbon Microspheres with a Double Carbon Matrix for Enhanced Cycling Performance of Lithium‐ion Batteries. Issue 15 (20th April 2022) - Cao, Yuhao; Liu, Xu; Liu, Yuansheng; Liu, Huitian; Dai, Xiaoqian; Wu, Xiaochen; Shan, Zhongqiang
Abstract: Limited by low electrical conductivity and huge volume changes in the process of lithium intercalation/de‐intercalation, the commercial application of Si‐based anode materials for lithium‐ion batteries is hindered. Herein, silicon nanoparticles embedded in nitrogen‐doped hard carbon microspheres composites (Si/NC@HC) were prepared by two‐step polymerization of 3‐aminophenol and resorcinol between formaldehyde and further carbonization. The formed double carbon matrix, including the inter NC microsphere and outer nanometer‐thick HC layer, can not only improve the electrical conductivity and silicon load but also ensure high structural stability to alleviate the volume effect of silicon effectively. Therefore, the obtained Si/NC‐2@HC possesses a high specific capacity of 1262.6 mAh g −1 after 300 cycles at the current density of 0.5 A g −1 with high silicon contents of 78 %, exhibiting excellent cycling performance. The novel synthesis method and structural design will provide a strategy for engineering Si‐based anode materials with high specific capacity and enhanced cycling performance. Abstract : In this work, silicon nanoparticles embedded in nitrogen‐doped hard carbon microspheres composites (Si/NC@HC) were prepared by polymerization of 3‐aminophenol and resorcinol between formaldehyde and further carbonization. Benefiting from the formed double carbon matrix, composed of inter NC microsphere and outer HC coating layer, the Si/NC@HC electrode has a high reversible specific capacity with excellent cycling stability as anode materials for lithium‐ion batteries.